A modified method of traction for young children with congenital dislocation of the hip as a preliminary to reduction - Ahmad Hata, Rasit (Malaysian Medical Association, 2004)
Many authors agree that preliminary traction prior to closed or open reduction for congenital dislocation of the hip is helpful. Different ways of traction have been used and each of them has its own advantages and disadvantages. One of the problems in the very young child is the difficulty in maintaining a suitable traction that is biomechanically effective. We found that using a rocker bed made the traction more "user friendly" for the child, the parent and the doctors.